Vascular Neurology Nurse Practitioner Provision of Telemedicine Consultations. (11th July 2010) - Demaerschalk, Bart M.; Kiernan, Terri-Ellen J.; Investigators, STARR
Abstract : Objective . The objective was to define and evaluate a role for the Vascular Neurology-Nurse Practitioner (VN-NP) in the delivery of telemedicine consultations in partnership with a vascular neurologist. Methods . Prospective stroke alert patients at participating hospitals underwent a two-way audio video telemedicine consultation with a VN-NP at a remotely located stroke center in partnership with a vascular neurologist. Demographic information, National Institutes of Health Stroke Scale (NIHSS) scores, diagnoses, CT contraindications to thrombolysis, thrombolysis eligibility, and time interval data were collected. The inter-rater agreement between VN-NP and vascular neurologist assessments was calculated. Results . Ten patients were evaluated. Four were determined to have ischemic stroke, one had a transient ischemic attack, two had intracerebral hemorrhages, and three were stroke mimics. Overall, three patients received thrombolysis. The inter-rater agreement between VN-NP and vascular neurologist assessments were excellent, ranging from 0.9 to 1.0. The duration of VN-NP consultation was53.2 ± 9.0 minutes, which included the vascular neurologist supervisory evaluation time of12.0 ± 9.6 minutes. Conclusion . This study illustrated that a stroke center VN-NP, in partnership with a vascular neurologist, could deliver timely telemedicine consultations, accurate diagnoses, and correct treatments in acute stroke patients who presented to remotely located rural emergency departments within a hub and spoke network. VN-NPs may fulfill the role of a telestroke provider.